AB163. Semi-conservative management for elderly patients with bilateral renal masses - Qi, Shiyong (Transl Androl Urol, 2016)
OBJECTIVE: To evaluate semi-conservative management for elderly patients with bilateral renal masses METHODS: We reviewed the clinical data of six cases which underwent semi-conservative management from July 2006 to July 2014 in our hospital. There were four males and two females. Average age was 71 years (range, 65–80 years). Each patient had two solid renal masses: one larger and one smaller. The six larger masses had an average diameter at diagnosis of 7.0 cm (range, 4.5–10.0 cm) and were performed with radical nephrectomy (RN). The six smaller had an average diameter of 2.3 cm (range, 1.8–2.7 cm) and were performed with conservative management. All patients were followed with computed tomography scan or abdominal ultrasound. Growth rate was calculated based on the tumor diameter and volume. RESULTS: There were no serious surgical complications. Pathology revealed renal cell carcinoma (RCC) in all six larger tumors (five clear cell RCC and one chromophobe cell RCC). All were prospectively followed with CT or abdominal ultrasound for a median of 34 months (range, 12–45 months). Mean tumor growth of the six smaller masses was 0.3 cm in diameter or 2.96 cm(3) in volume per year, and there was no sign of local invasion or distant metastasis. No recurrence was found in operative lateral and no evidence of metastasis. CONCLUSIONS: Semi-conservative management is safe and effective for elderly patients with bilateral renal masses (one larger and one smaller).